2017
DOI: 10.5861/ijrsp.2017.1735
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-esteem and loneliness among university students living in hostels

Abstract: The present study was intended to explore the relationship between self-esteem and loneliness among University Hostel Living students. It was hypothesized that there would be a negative correlation between self-esteem and loneliness. The sample of this study was comprised of (N= 400) university students whose age ranging from 18 year to 24 year and living in hostels.Sample was drawn from different Universities from Punjab, Pakistan which consisted of almost equal numbers of males (n = 198) and females (n = 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Additionally, the results obtained between self-esteem and loneliness, another result of direct effects, are consistent with previous results. For instance, Ishaq et al, (2017) uncovered a strong negative correlation between self-esteem and loneliness in a study they conducted on university students. Apart from this, there are other studies that focus on the relationships between self-esteem and loneliness and support this research result (Iranmanesh et al, 2019;Shi et al, 2017;Varghese & Pistole, 2017).…”
Section: Discussion On the Direct Effects In The Modelmentioning
confidence: 99%
“…Additionally, the results obtained between self-esteem and loneliness, another result of direct effects, are consistent with previous results. For instance, Ishaq et al, (2017) uncovered a strong negative correlation between self-esteem and loneliness in a study they conducted on university students. Apart from this, there are other studies that focus on the relationships between self-esteem and loneliness and support this research result (Iranmanesh et al, 2019;Shi et al, 2017;Varghese & Pistole, 2017).…”
Section: Discussion On the Direct Effects In The Modelmentioning
confidence: 99%
“…Yang berarti jika harga diri semakin rendah maka semakin tinggi kesepian. Ishaq et. al, (2017) juga menemukan perbedaan jenis kelamin tidak berkontribusi terhadap kesepian dan harga diri secara signifikan.…”
Section: Pendahuluan Latar Belakangunclassified
“…In one of such research Javed and Tariq, (2016) found a difference between career decision making difficulties in male and female, where no difference found across gender in self-esteem. In another work Ishaq, Malik and Asif (2018) investigated self-esteem, loneliness and psychological wellbeing in female and male students who are living in dormitory, made an inference that loneliness affect wellbeing with moderating effect of selfesteem with male having higher self-esteem and well-being score. Pakistan is one of the populous country in the world with diversification in culture, languages and religion.…”
Section: Introductionmentioning
confidence: 99%